Quantitative "Versus" Qualitative Research: The Wrong Question - Olson, Hope (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Through a deconstructive reading of texts on qualitative method and its contrast with quantitative method and through information needs studies regarding specific populations of women this paper concludes that the focus on method should not drive research. Rather, the ontological and epistemological stances of researchers assessed on a spectrum from subjective to objective are more indicative of the perspectives represented in library and information science research. Avec un étude déconstructif des textes sur des méthodes qualitatives et ses contrastes avec des méthodes quantitatives et avec l'étude des besoins informatiques à l'égard des populations spécifiques de femmes cette document conclut que le focus sur les méthodes utilisées ne devrait pas motiver la recherche. Au lieu, les positions ontologiques et épistemologiques des chercheurs évaluées sur une gamme du subjectif à l'objectif sont plus indicatives des perspectives représentées dans la domaine de la bibliothéconomie et des sciences de l'information.